2013
DOI: 10.11646/zootaxa.3686.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Description and distribution of two new species of Paraonidae (Annelida: Polychaeta) from a lagoon-estuarine ecosystem in the Southern Gulf of Mexico 

Abstract: The aim of this study was to analyze the taxonomy and distribution of the polychaetes of the family Paraonidae from a lagoon-estuarine ecosystem in the Gulf of Mexico. The samples come from 20 soft bottom stations in the Términos Lagoon during the dry and rainy seasons, of which eight included paraonids. In all, 1183 specimens belonging to two new species were identified: Aricidea (Acmira) hirsuta (1125 specimens) and Paradoneis carmelitensis (58 specimens). A. (A.) hirsuta is clearly distinguished from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…All this suggests that future research efforts, including the description of new species (Arriaga-Hernández et al, 2013), could significantly increase the biodiversity values found inside the lagoon. It is necessary to emphasize that the polychaetes are usually the dominant macrofaunal group in tropical estuaries (Gambi et al, 1997), and are characterized by their high tolerance to severe daily and seasonal environmental variations, allowing them to reach high abundances in those environments (Dittman, 2000;Gambi et al, 1997;Rosa-Filho et al, 2005;Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…All this suggests that future research efforts, including the description of new species (Arriaga-Hernández et al, 2013), could significantly increase the biodiversity values found inside the lagoon. It is necessary to emphasize that the polychaetes are usually the dominant macrofaunal group in tropical estuaries (Gambi et al, 1997), and are characterized by their high tolerance to severe daily and seasonal environmental variations, allowing them to reach high abundances in those environments (Dittman, 2000;Gambi et al, 1997;Rosa-Filho et al, 2005;Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The confirmation of the taxonomic status of the new species was based on the excellent revision and compilation of the diagnostic characteristics of all recognized species of the subgenera Aricidea (Acmira) and Aricidea (Aricidea) by Blake (1996), Lovell (2002) and Arriaga-Hernández et al (2013). For comparative purposes, a table with the main diagnostic characters of the new species and closely related species was also included.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the subgenus Aricidea (Acmira) Hartley, 1981 is represented by 20 species, including the new species described in the present study. The species that make up this subgenus can be separated by the features of modified neurochaetae (teeth, hood, distal arista, and pubescence), the length and shape of the median antenna, the number of prebranchial chaetigers and the number of branchiae (Arriaga-Hernández et al 2013). Previously, only one species, A.…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the number of new species described recently [12][13][14][15][16], for both monotypic genera, Aparaonis and Sabidius, no additional species has been described since the original descriptions of Aparaonis abyssalis Hartman, 1965 [4] and Sabidius cornatus (Hartman, 1965) [4]. Although the former species is known from a single specimen [10], members of the latter have been found in several other surveys [2,10,17,18].…”
Section: Introductionmentioning
confidence: 99%